2014
DOI: 10.5958/0974-0279.2014.00019.6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Yields of Major Food Crops in India: Implications for Food Security

Abstract: The study has analysed changes in climate variables, viz. temperature and rainfall during the period 1969-2005 and has assessed their impact on yields of important food crops. A significant rise was observed in mean monthly temperature, but more so during the post-rainy season. The changes in rainfall, however, were not as significant. While an increase in maximum temperature was found to have an adverse effect on the crop yields, a similar increase in minimum temperature had a favourable effect on yields of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 26 publications
5
107
2
2
Order By: Relevance
“…This implies that higher rainfall and maximum temperature would mean lower the rice yield rates. The rice results are not consistent with Gupta et al () but more or less similar with Birthal et al (). The reason for not getting similar results might be the different data series and time periods.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…This implies that higher rainfall and maximum temperature would mean lower the rice yield rates. The rice results are not consistent with Gupta et al () but more or less similar with Birthal et al (). The reason for not getting similar results might be the different data series and time periods.…”
Section: Resultscontrasting
confidence: 69%
“…Using these methods, several studies have assessed the effect of weather change on crop output across the world (for instance see Sarker et al, ; Agba et al, ; Zhang, Zhang, & Chen, ; Sbaouelgi, ; Attiaoui & Boufateh, ). Some of the studies employing the econometric models to examine effects of weather variation on crop productivity in India include Guiteras (), Moorthy, Buermann, and Rajagopal (), Barnwal and Kotani (), Gupta et al (), Birthal et al (), Farook and Kannan (), Nath and Mandal (), and Pal and Mitra (). Lastly, the overview of the literature reported that changes in climate have an adverse effect on food and non‐food production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In India, agricultural production activities play a significant role to provide SLS, employment opportunities, food security and poverty alleviation, as around 54% Indian workforce are engaged in agricultural [23][24][25]. In India, agricultural sector feeds vast population which stands second on the world.…”
Section: Sustainable Livelihood Security In Indiamentioning
confidence: 99%
“…The surveyed farm-households had experienced and managed complex and heterogeneous environments to cultivate rain-fed crops using their indigenous knowledge in the past. But recent reported abrupt changes to the local climate (Birthal et al 2014), indicated by fluctuating air temperatures and precipitation, has substantially affected local weather and impacted Kharif crop production. In addition, under marginal growing conditions, local crop varieties have resulted in a loss of competitiveness and lower productivity levels.…”
Section: Agriculture Nutrition and Their Disconnectmentioning
confidence: 99%